Seed morphology and post-seminal development in species of Comanthera (Eriocaulaceae) - Dugarte Corredor, Blanca Auxiliadora [UNESP]; Escobar Escobar, Diego Fernando [UNESP]; Scatena, Vera Lucia [UNESP] (Revista De Biologia Tropical, 2015)
Comanthera brasiliana, C. magnifica and C. suberosa (Eriocaulaceae) are included in the Brazilian list of endangered species, due to intensive harvest and micro-endemism. These species form the Glade of Comanthera magnifica, along with C. brunnea and C. linearis. Germination, seed morphology and post-seminal development were studied aiming to characterize all five species and to provide information for their conservation. Seeds were collected in campos rupestres of Minas Gerais, Brazil. Seed morphology was examined using scanning electron microscope. For germination tests, mature seeds were placed in Petri dishes lined with filter paper dampened with distilled water at 25 C and fluorescent light; four repetitions with 15 seeds were performed for each species. For the anatomical analysis of post-seminal development, seedlings at different developmental stages were included in historesin, cut with a rotatory microtome and examined under a light microscope. The structure of the seed coat and the shape and size of the seeds were characteristics that allowed species differentiation, and based on the seeds morphological characteristics, an identification key is provided. The seed germination was high (> 90 %) and fast (< 7 days). Germination occured through the axis protrusion of the embryo. Approximately four days after germination, the first leaf develops and is followed by the adventitious roots. After 10-15 days, the second leaf and the new adventitious roots develop. In field conditions, the studied species occur in quartzite soils and their small seeds (dust-like type) germinate faster than the other Eriocaulaceae species (from mesic soils). These results provide reliable information that may contribute to the species management and conservation.
Keywords: Comanthera; Eriocaulaceae; seed morphology; germination; everlasting plants; Brazil